EVALUATION OF EFFECTS OF EXPERIMENTAL EXOGENOUS FEVER, HYPERTHERMIA AND VARIOUS DRUGS ON INFANT RAT BRAIN - Aydin, Mustafa; Girgin, Feyza Incekoy; Kabakus, Nimet; Ayar, Ahmet; Canatan, Halit; Bulmus, Ozgur; Sen, Yasar (Nobel Ilac, 2012)
Objective: Hyperthermia may cause pathological changes in all systems and organs including the brain. Neuronal effects of exogenous fever (39 degrees C) and hyperthermia (41 degrees C), and efficacy of different medication modalities were studied in two-week-old infant female Wistar-Albino rats. Material and Method: Possible neuronal damage was evaluated by examining healthy, apoptotic and necrotic cells, and heat shock proteins (HSP, HSP 27 and HSP 70) in the cerebral cortex, cerebellum, and hypothalamus. Results: In both temperature groups, convulsion has been observed at different rates (25-37.5%). Three infant rats with convulsion in the group of 41 degrees C temperature were died (n=3/9, 33.3%). At cellular level, when all neural tissues were taken into account; (i) considerable increase in number of necrotic neurons in both temperature groups (p=0.001, p=0.000), (ii) after 39 degrees C fever, a decrease in number of healthy cells by diclofenac medication (p=0.02), an increase in number of necrotic cells by dexamethasone (p=0.02) and diclofenac (p=0.005) medications, (iii) after 41 degrees C hyperthermia, a decrease in number of necrotic cells by dexamethasone (p=0.000) and paracetamol medications (p=0.000) were observed. In the group of 39 degrees C fever, all medications were ineffective in terms of the number of apoptotic cells (p>0.05). Conclusion: In conclusion, results of the present study showed that neuronal tissue of various brain regions responded as different degree of damage or improvement to hyperthermic time course and applied medications. It was considered that these conflicting data might be due to the complexity of the brain.
Keywords: Fever; hyperthermia; brain; neurons